Design of a photovoltaic based Electric Vehicle (EV) charging station - Riful, Golam Rasul; Sarker, Pronoy; Shawon, Sajjad Hossain; Hasan, Md Mahmudul (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.